ANALISIS KARYA MUSIK PADA ANSAMBEL KOPER DI SMA MUHAMMADIYAH 1 PONTIANAK - Sanjaya, Ridho Novreza; Mering, Aloysius; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe destination goals of this research were to describe the process of creation, analysis, and implementation of the work presented by Koper ensemble in SMA Muhammadiyah 1 Pontianak on art and culture subjects. The method used in this research was descriptive analysis method with qualitative research form. The approach used was the musical approach. The forms of data used in this research were in the form of speech, interview, video recording, photo resource, and information from members of Koper ensemble about the works. Research data were obtained from various sources; such as composers of Koper ensemble, members of Koper ensemble, and art and culture teacher at SMA Muhammadiyah 1 Pontianak. The informants who were the sources of this research were Rolly Pierdian, Deandy Dozan, Faisal Malik, and Ahmad Rayhan. To test the validity of the data, researcher used the source triangulation technique. Based on the results of data analysis on the ensemble piece of Koper ensemble in SMA Muhammadiyah 1 Pontianak, the researcher can conclude that the process of creating the work of Koper ensemble has 3 stages, namely the determination of ideas, selection of instruments, and pattern making. In the notation writing, the researcher chose 3 works as the sample. These works are Malam Sepi Membara by Deandy Dozan, Naek Pesawat by Faisal Malik, and Senja by Ahmad Rayhan. The musical works of the Koper ensemble at SMA Muhammadiyah 1 Pontianak can be taught through the subjects of Cultural Arts and Skills (SBK) on the standards of competence: expressing themselves through musical artwork and basic competence: identifying musical artwork.  Keywords: musical works creation process, musical works analysis, implementation, Koper ensemble, SMA Muhammadiyah 1 Pontianak